2014
DOI: 10.1177/1758573213517218
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes following a physiotherapy rehabilitation programme for atraumatic posterior shoulder subluxation

Abstract: Received

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Exercise was the most frequently cited treatment intervention reported by respondents for managing the clinical vignettes, which is supported by expert opinion and the limited research available supporting non-surgical management of ASI [ 27 , 30 , 48 50 ]. Interestingly, physiotherapists reported adapting their exercise approach depending upon the clinical scenario, aligning with expert recommendations [ 9 , 13 ] but in conflict with the evidence supporting the clinical effectiveness of standardised rehabilitation protocols [ 27 29 , 48 ].…”
Section: Discussionmentioning
confidence: 93%
“…Exercise was the most frequently cited treatment intervention reported by respondents for managing the clinical vignettes, which is supported by expert opinion and the limited research available supporting non-surgical management of ASI [ 27 , 30 , 48 50 ]. Interestingly, physiotherapists reported adapting their exercise approach depending upon the clinical scenario, aligning with expert recommendations [ 9 , 13 ] but in conflict with the evidence supporting the clinical effectiveness of standardised rehabilitation protocols [ 27 29 , 48 ].…”
Section: Discussionmentioning
confidence: 93%
“…The study will be powered to detect a between-group difference equal to or greater than a previously reported clinically important change of 252 points [ 40 , 63 ], with an SD for change from baseline to the 16-week follow-up of 350 points [ 16 , 22 ]. We expect both groups to experience a clinically relevant improvement, seen as a 48% improvement in the HEAVY group (equal to 504 points with an expected baseline mean score of 1050 points) comparable with effects of previous interventions [ 16 , 18 , 22 , 34 , 64 , 65 ] and 24% improvement in the LIGHT group [ 18 ] (equal to 252 points with an expected baseline mean score of 1050 points). With a two-sided significance level of 0.05 and 90% power, a sample size of 42 per group is required to detect a statistically significant difference.…”
Section: Interventionsmentioning
confidence: 93%
“…In the intention-to-treat and per-protocol analyses, missing data at follow-up will be accounted for by using a multiple imputation technique with age, sex, group allocation (masked), and baseline values as predictors. For sensitivity purposes, missing data will be imputed using a non-responder imputation, in which baseline values are carried forward [ 65 ]. The rationale builds on the assumption that participants who drop out will return to their baseline WOSI score [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…The number of participants receiving physiotherapy was approximately 491 ranging from 15 [27] to 85 [16]; one study reported the number of shoulders rather than participants [28]. The mean age of participants was similar between studies, ranging from 16 [29] to 25 years [28]. Proportions of female participants ranged from 53% [29] to 80% [17].…”
Section: Study Characteristicsmentioning
confidence: 99%